Off-task behavior in elementary school children. (August 2016) - Godwin, Karrie E.; Almeda, Ma. V.; Seltman, Howard; Kai, Shimin; Skerbetz, Mandi D.; Baker, Ryan S.; Fisher, Anna V.
Abstract: This paper reports results from a large-scale observational study investigating attention allocation during instructional activities in elementary school students (kindergarten through fourth-grade). In Study 1, 22 classrooms participated while a more diverse sample of 30 classrooms participated in Study 2. This work investigated temporal patterns in children's attention allocation by collecting observational data on children's on- and off-task behaviors at three different time points (i.e., beginning, middle, and end of the school year) [Study 1]. We also investigated whether patterns of attention allocation changed as a function of student characteristics (gender, grade-level, SES), teachers' instructional design choices (instructional format and duration of an instructional activity), and school type (private, parochial, public charter schools) [Studies 1 & 2]. Children's patterns of attention allocation fluctuated over the course of the school year. Female students were found to be more on-task compared to male students. On-task behavior tended to decline as the instructional duration increased. The lowest rates of on-task behavior were observed while children were engaged in whole-group instructional formats. An effect of school type was found with higher proportions of on-task behavior observed in parochial schools. However, the effect of grade-level was equivocal across studies. These findings can begin to form a foundation for the development of research-based guidelines for instructional design aimed to support engagement among students in elementary classrooms. Highlights: On-task behavior declined at the end of the school year. On-task behavior declined as instructional duration increased from 10 to 30 min. Lowest rates of on-task behavior were observed in whole-group instructional formats. Girls were more likely to engage in off-task peer interactions than boys. Overall, girls were more likely to be on-task than boys.